Steroid myopathy in patients with myasthenia gravis: a literature review - S. A. Zaytsevskaya; N. A. Suponeva; K. V. Antonova; D. A. Grishina; A. M. Narbut (Нервно-мышечные болезни)
Steroid myopathy is a common drug-induced non-inflammatory myopathy that affects patients requiring long-term glucocorticoid treatment for various autoimmune, inflammatory and oncological diseases. According to the neurology clinical practice guidelines, non-fluorinated glucocorticoids are the first-line pathogen-directed therapy for a number of dysimmune neuromuscular disorders, including myasthenia gravis. Long-term high-dose steroid treatment regime for myasthenia gravis leads to both acute and chronic development of glucocorticoids-induced proximal muscle weakness and atrophy. Steroid myopathy, along with other undesirable side effects of glucocorticoids therapy, impact health-related quality of life, patient satisfaction and adherence to treatment. Hence, further studies are required to expand our knowledge of clinical evaluation, diagnostic testing and prevention approaches for glucocorticoids-induced myopathy. The aim of this literature review is to analyze existing data on pathogenesis, diagnostic tools and treatment strategies for steroid myopathy.